Monitoring of Cerebral Blood Flow and Metabolism Bedside in Patients with Subarachnoid Hemorrhage – A Xenon-CT and Microdialysis Study - Rostami, Elham; Engquist, Henrik; Johnson, Ulf; Howells, Timothy; Ronne-Engström, Elisabeth; Nilsson, Pelle; Hillered, Lars; Lewén, Anders; Enblad, Per (Frontiers in Neurology, 2014)
Cerebral ischemia is the leading cause of morbidity and mortality following aneurysmal subarachnoid hemorrhage (SAH). Although 70% of the patients show angiographic vasospasm only 30% develop symptomatic vasospasm defined as Delayed cerebral ischemia (DCI). Early detection and management of reversible ischemia is of critical importance in patients with SAH. Xenon computerized tomography (Xenon-CT) using a bedside CT scanner makes it possible to measure quantitative regional Cerebral blood flow (CBF) bedside in the neurointensive care (NIC) setting and intracerebral microdialysis is a method that offers the possibility to monitor the metabolic state of the brain continuously. Here we present results on nine SAH patients with both microdialysis monitoring and bedside Xenon-CT measurements. CBF measurements were performed within the first 72h following bleeding. Six out of nine patients developed DCI at a later stage. Five out of six patients who developed DCI had initial global CBF below 26 ml/100g/min whereas one had 53 ml/100g/min. The 3 patients who did not develop clinical vasospasm all had initial global CBF above 27 ml/100g/min. High Lactate/Pyruvate ratio was associated with lower CBF values in the area surrounding the catheter. Five out of nine patients had Lactate/Pyruvate ratio ≥ 25 and four of these patients had CBF ≤ 22 ml/100g/min. These preliminary results suggest that patients with initially low global CBF on Xenon-CT may be more likely to develop DCI. Initially low global CBF was accompanied by metabolic disturbances determined by the microdialysis. Most importantly, pathological findings on the Xenon-CT and microdialysis could be observed before any clinical signs of DCI. Combining bedside Xenon-CT and microdialysis was found to be useful and feasible. Further studies are needed to evaluate if delayed cerebral ischemia can be detected before any other signs of DCI to prevent progress to infarction.